Severity of white matter hyperintensities in older adults aged in their mid 80s and its relationship with hemodynamic and cardiac parameters. (December 2015) - Todoroki, Kikue; Ikeya, Yoshimori; Fukui, Sayato; Yanagimachi, Noriharu; Okazaki, Takashi; Tanaka, Chiharu; Tanaka, Etsuro; Shizuma, Toru; Fukuyama, Naoto; Mori, Hidezo
Abstract : Aim: In the present study, we analyzed the severity of white matter hyperintensities detected on magnetic resonance imaging of the brain in older Japanese adults who were aged in their mid 80s, and examined its relationships with the clinical parameters. Methods: To identify factors related to the severity of white matter hyperintensities in 33 older adult attendees of our outpatient clinic and 17 older adults living in a group home, we carried out logistic regression analyses and/or correlation analyses. Results: Cognitive function and activities of daily living were significantly correlated with the severity of white matter hyperintensities. Multivariate analysis identified activities of daily living, but not cognitive function, as being independently associated with the severity of white matter hyperintensities. Several hemodynamic and cardiac parameters, including diastolic blood pressure, hemoglobin, serum level of N‐terminal pro‐brain natriuretic peptide, cardiothoracic ratio on the chest X‐ray, severity of supraventricular arrhythmias on a Holter electrocardiogram and serum levels of docosahexaenoic acid, were significantly correlated with the severity of white matter hyperintensities. In contrast, the serum cholesterol, glycosylated hemoglobin value and systolic blood pressure were not correlated with the severity of white matter hyperintensities. Conclusions: The severity of white matter hyperintensities detected on magnetic resonance imaging of the brain in older Japanese patients aged in their mid 80s was significantly correlated with activities of daily living, hemodynamic and cardiac parameters, and the serum level of docosahexaenoic acid. Geriatr Gerontol Int 2015; 15 (Suppl. 1): 66–73.